A facile CO2 switchable nanocomposite with reversible transition from sol to self-healable hydrogel1. Issue 76 (19th August 2015) - Zhang, Lei; Qian, Jiasheng; Fan, Yujiao; Feng, Wei; Tao, Zhen; Yang, Haiyang
<x xml:space="preserve">Abstract</x> We demonstrated a facile CO2 switchable nanocomposite system with reversible transition from sol to self-healable hydrogels.